PEMBERIAN AMELIORAN PADA TAILING UNTUK MENINGKATKAN PERTUMBUIHAN KEMIRI (Alaurites moluccana (L) Wild DI PERSEMAIAN - . Gustian; . Burhanuddin; Wiwik Ekyastuti (Tengkawang : Jurnal Ilmu Kehutanan, 2017)
Gold mining activities have negatively impacted post-mining land into poor nutrients, low pH, toxic soil, due to heavy metal content, low water holding capacity, low organic matter content and unstable land conditions. To change the tailings to be more productive many of the available technologies, such as the use of manure, compost, litter or the use of soil microbes such as mycorrhiza. The addition of manure can additionally increase nutrient available, can also improve the physical and biological properties of the soil. Alaurites moluccana (L) Wild) is one of the plants classified as a pioneer species because it can grow on critical land with low soil fertility and open soil. Research on ameliorant of tailings to increase the growth of  A. moluccana  in the nursery aims to obtain a mixture of ameliorants with the tailings to enhance the growth of A. moluccana  in the nursery. Treatment was given to the growth of seedlings of A. moluccana  using the Completely Randomized Design (RAL) exprotment method with a total of 8 treatments that included an ameliorant tailing control, tailings with ameliorant a (1: 1, 1: 2, and 1: 3), tailings with ameliorant b (1: 1, 1: 2, and 1: 3) and ultisol soil control, with each treatment repeated 5 times. Data collected were shoot hight (cm), stem diameter (mm), number of leaves and dry weight of plant. The result of tailings treatment  with addition of organic ameliorant gave a very significant effect on the growth of height, diameter, number of leaves and dry weight of the A. Moluccana.  The best media treatment for all parameters is M6 (tailings: kotoran sapi 1: 3). Although virtually all treatments with organic ameliorant  provide better results than controls without the addition of organic ameliorants.Keywords: Tailings, ameliorant, A. moluccana , organic.